Cytomegalovirus-Specific IL-10-Producing CD4+ T Cells Are Governed by Type-I IFN-Induced IL-27 and Promote Virus Persistence. - Mathew Clement; Morgan Marsden; Maria A Stacey; Juneid Abdul-Karim; Silvia Gimeno Brias; Diana Costa Bento; Martin J Scurr; Peter Ghazal; Casey T Weaver; Gianluca Carlesso; Simon Clare; Simon A Jones; et al. (PLoS Pathogens)
CD4+ T cells support host defence against herpesviruses and other viral pathogens. We identified that CD4+ T cells from systemic and mucosal tissues of hosts infected with the β-herpesviridae human cytomegalovirus (HCMV) or murine cytomegalovirus (MCMV) express the regulatory cytokine interleukin (IL)-10. IL-10+CD4+ T cells co-expressed TH1-associated transcription factors and chemokine receptors. Mice lacking T cell-derived IL-10 elicited enhanced antiviral T cell responses and restricted MCMV persistence in salivary glands and secretion in saliva. Thus, IL-10+CD4+ T cells suppress antiviral immune responses against CMV. Expansion of this T-cell population in the periphery was promoted by IL-27 whereas mucosal IL-10+ T cell responses were ICOS-dependent. Infected Il27rα-deficient mice with reduced peripheral IL-10+CD4+ T cell accumulation displayed robust T cell responses and restricted MCMV persistence and shedding. Temporal inhibition experiments revealed that IL-27R signaling during initial infection was required for the suppression of T cell immunity and control of virus shedding during MCMV persistence. IL-27 production was promoted by type-I IFN, suggesting that β-herpesviridae exploit the immune-regulatory properties of this antiviral pathway to establish chronicity. Further, our data reveal that cytokine signaling events during initial infection profoundly influence virus chronicity.